Analola Santana. Freak Performances: Dissidence in Latin American Theater. U of Michigan P, 2018. - Stephanie R Orozco (Studies in 20th & 21st Century Literature, 2021)
Review of Analola Santana. Freak Performances: Dissidence in Latin American Theater. U of Michigan P, 2018. 266 pp.
Keywords: theater; disability studies; queer studies